Knowledge of Cervical Cancer and Cervical Cancer Screening Methods Among Female Secondary School Students in Ibadan, Nigeria (African Journal of Biomedical Research, 2020)
Cervical cancer is the most common cancer of the female genital tract worldwide and a leading cause of cancer-related deaths. For many years, the cervical Papanicolaou smear or Pap Test has been the standard method for cervical cancer screening. Screening with a Pap test has been shown to reduce the cervical cancer incidence by 60-90% and mortality by up to 90%, especially when more than 70% of those at risk accessed the test. The objective of the current study was to ascertain the level of knowledge of screening for cervical cancer among female secondary school pupils, since they were or would soon be at risk of the disease. This cross-sectional descriptive study recruited 361 female secondary students from three different schools in Ibadan.  Data were obtained over a period of five months, using a structured self-administered questionnaire, and analysed using the Statistical Package for Social Sciences (SPSS) version 22. Of the 361 respondents aged 10 to 21, 78.7% had heard about cervical cancer but only 11% had good knowledge about it. Nearly 85% of the respondents had never heard about cervical cancer screening methods. Pupils attending private schools were more likely to have a better knowledge of cervical cancer screening methods than those attending public schools (p < 0.001). Majority of the secondary school students were not equipped with sufficient knowledge about cervical cancer, its causation and the screening methods to prevent it. Such information ought to be included in the curricula of secondary schools